Can Real Options Explain the Skewness of Stock Returns? - Ho, Tuan; Kim, Kirak; Li, Yang; Xu, Fangming (Journal of Banking & Finance, 2023)
We study a novel mechanism through which real options play a prominent role in inducing the skewness of stock returns. Building on the investment-based asset pricing framework, we show that firms’ real options to contract (expand) their businesses when productivity is low (high) can increase return skewness. Consequently, return skewness represents a U-shaped function of firm productivity. Furthermore, the real-options effect is stronger for more flexible firms, characterized by lower scale-adjustment frictions. Employing a large sample of U.S. firms during 1972–2018, we provide a battery of robust empirical evidence consistent with the model predictions. Our findings demonstrate that firm-level real flexibility can impact investors and managers’ decision making.